2006
DOI: 10.1097/01.aids.0000238417.05819.40
|View full text |Cite
|
Sign up to set email alerts
|

DEFB1 gene polymorphisms and increased risk of HIV-1 infection in Brazilian children

Abstract: In our study we analysed three single nucleotide polymorphisms (SNPs) in the 5' untranslated region (UTR) of the DEFB1 gene, namely -52(G/A) -44(C/G) and -20(G/A), in three groups of northeastern Brazilian children in order to assess their role in HIV-1 infection. Our results allowed us to hypothesize that the SNPs located in the 5' UTR of the DEFB1 gene can be employed as a marker of risk for HIV-1 infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 7 publications
2
49
0
Order By: Relevance
“…Although the anti-HIV-1 role of HBD-1 has not been previously reported, an association between SNPs in DEFB1 and the risk of acquiring HIV-1 infection has been suggested (44)(45)(46)(47). In our group, studies have indicated that the A692G polymorphism is associated with resistance to HIV-1 infection among discordant couples (42).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Although the anti-HIV-1 role of HBD-1 has not been previously reported, an association between SNPs in DEFB1 and the risk of acquiring HIV-1 infection has been suggested (44)(45)(46)(47). In our group, studies have indicated that the A692G polymorphism is associated with resistance to HIV-1 infection among discordant couples (42).…”
Section: Discussionmentioning
confidence: 70%
“…Previous SNP studies have suggested that -44 C/G (site 668), -20 A/G (site 692) and -52 G/A (site 660) SNPs in DEFB1 are associated with differential risks of vertical transmission of HIV-1 (44)(45)(46)(47). Furthermore, the frequency of the SNP genotype A692G G/G in the DEFB1 gene was significantly higher in ESN compared to SP individuals and suggested an association of this SNP with resistance to HIV-1 infection (42).…”
mentioning
confidence: 99%
“…In line with the widespread expression of HBD1 and therefore its seemingly grave importance in epithelial defense, the variant also holds relevance in additional clinical contexts, e.g. in HIV transmission (Braida et al, 2004;Milanese et al, 2006) and oral infections (Jurevic et al, 2003). The SNP is generally functionally linked to HBD1 mRNA level, and interestingly also involved in the transcriptional expression of HBD3, at least in keratinocytes (Kalus et al, 2009).…”
Section: Gut Defensinsmentioning
confidence: 95%
“…34,35 These -20A/-44C/-52G haplotypes have all been associated with chronic lung infection with P. aeruginosa. 36 The -44C allele also predisposes to infection by HIV 37,38 and Candida spp. 39 Moreover, Carter et al also found that it strongly associated with endophthalmitis.…”
Section: Immune Response and Risk Factorsmentioning
confidence: 99%